1978
DOI: 10.1029/gl005i001p00059
|View full text |Cite
|
Sign up to set email alerts
|

The latitudinal, diurnal, and altitudinal distributions of upward flowing energetic ions of ionospheric origin

Abstract: Upward flowing fluxes of energetic (0.5‐16 keV) H+ and O+ ions are frequently observed by the ion mass spectrometer on the polar‐orbiting S3‐3 satellite. Data obtained on the first ∼370 orbits have been used to derive the occurrence frequency of these fluxes. The upward acceleration of ionospheric ions to keV energies is a persistent phenomenon generally occurring in a zone closely associated with the statistical auroral oval. Upward flowing ion events with flux above ∼2 × 106 keV/(cm² sec ster keV) are observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
137
1

Year Published

1980
1980
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 334 publications
(143 citation statements)
references
References 16 publications
5
137
1
Order By: Relevance
“…Previous statistical analyses of satellite data (e.g. Ghielmetti et al, 1978;Loranc et al, 1991) have revealed that the spatial distribution of up¯ows is auroral oval-like. A statistical study of transversely accelerated ions (TAIs), and subsequent ion up¯ow, by Klumpar (1979) revealed a similar distribution of events, although the author reported ion¯uxes that were one to two orders of magnitude less than those observed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Previous statistical analyses of satellite data (e.g. Ghielmetti et al, 1978;Loranc et al, 1991) have revealed that the spatial distribution of up¯ows is auroral oval-like. A statistical study of transversely accelerated ions (TAIs), and subsequent ion up¯ow, by Klumpar (1979) revealed a similar distribution of events, although the author reported ion¯uxes that were one to two orders of magnitude less than those observed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Magnetotail ion composition measurements in that energy range were first made more than 20 years ago on the ISEE 1 satellite, within 23 R E [Lennartsson and Shelley, 1986, and references therein], and are presently being made with the Cluster satellites within 19 R E [e.g., Rème et al, 2001]. Near-Earth ion composition measurements ($2 R E ) were begun even earlier with the polar-orbiting S3-3 satellite and were indeed the first to both detect the energetic ion outflow and provide substantial statistical material [e.g., Ghielmetti et al, 1978;Collin et al, 1981]. Similar measurements were subsequently extended as far as R $ 6 R E with the Prognoz-7 satellite [Lundin et al, 1983] and R $ 4.5 R E with the DE 1 satellite [e.g., Yau et al, 1984Yau et al, , 1985aYau et al, , 1985b, the latter being especially pivotal in that they were made continually over almost 10 years; that is almost a complete solar cycle.…”
Section: Introductionmentioning
confidence: 99%
“…In support of the latter process, GHIELMETTI et al (1978) have reported the common occurrence of upward flowing energetic ions (both W and 0+) of ionospheric origin, especially in the afternoon and evening sectors (see Fig. 3).…”
Section: Energetic-particle Access To the Magnetospherementioning
confidence: 99%